2020
DOI: 10.1177/2158244020957052
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Classroom to Enhance Academic Vocabulary Learning in an English for Academic Purposes (EAP) Course

Abstract: The present study explores the efficiency of the flipped classroom approach on English for Academic Purposes (EAP) students’ academic vocabulary acquisition in comparison with the conventional teaching approach. The efficiency is examined by evaluating students’ post-test performance, self-perceived mental effort employed in completing post-test tasks, and perceptions regarding the learning experiences. To this end, 60 undergraduates divided into flipped (E) and conventional (C) group participated in the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…Parents support this assessment with arguments stating that the range of everyday obligations does not allow them to fully and devotedly dedicate themselves to learning and full involvement in school obligations. Therefore, it is important that teachers apply to teaching approaches that will more clearly present the studied theoretical concepts (Jovanović et al, 2017;Knežević et al, 2020;Radulovic & Stojanovic, 2019;) and connect information into one coherent image (Trivić et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Parents support this assessment with arguments stating that the range of everyday obligations does not allow them to fully and devotedly dedicate themselves to learning and full involvement in school obligations. Therefore, it is important that teachers apply to teaching approaches that will more clearly present the studied theoretical concepts (Jovanović et al, 2017;Knežević et al, 2020;Radulovic & Stojanovic, 2019;) and connect information into one coherent image (Trivić et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, textbooks often include words that appear once without repetition, a vital element for vocabulary acquisition (Nation, 2013). Since explicit or intentional vocabulary learning benefits ESL learners more (Schmitt, 2010), many strategies for academic vocabulary learning in past studies have also stressed explicit ways (Goodwin et al, 2012;Knežević et al, 2020;Sibold, 2011;Sulaiman et al, 2018;Tan & Goh, 2020). Furthermore, according to Gallagher et al (2019), ESL learners are less likely to benefit from the incidental instruction of academic words.…”
Section: Challenges In Learning the Academic Vocabularymentioning
confidence: 99%
“…Hence, there are many reasons why ESL learners perceive the integration of web-based learning in a traditional classroom for vocabulary learning positively. For instance, multi-media materials are noted to increase the effectiveness of learning new words by assisting learners in developing self-learning methods for active and deeper learning (Fayaz & Ameri-Golestan, 2016), leading thereby to higher vocabulary gains (Knežević et al, 2020).…”
Section: The Use Of Web-based Learningmentioning
confidence: 99%
“…One of the tasks of the research was to examine the representation and motivational role of the application of information and communication technologies in the teaching process. The results of previous research have shown that the use of ICT encourages motivation to learn, encourages cooperation between students and teachers, as well as interactivity (Radulović, 2021;Sabzian, Gilakjani Olić Ninković, S., Adamov, J, & Makivić, N. (2022).Encouraging the motivation of students in primary school -a case study, International Journal of Cognitive Research in Science,Engineering and Education (IJCRSEE),10(1),[127][128][129][130][131][132][133][134][135][136] and Sodouri, 2013), and contributes to higher student achievement (Knežević, Županec and Radulović, 2020;Radulović, Stojanović and Županec, 2016;Radulović and Stojanović, 2019;Shapely, Maloney and Caranikas-Walker, 2010).…”
Section: Use Of Information and Communication Technologymentioning
confidence: 99%